Design of Robust Steerable Broadband Beamformers incorporating Microphone Gain and Phase Error Characteristics - Lai, Chiong; Nordholm, Sven; Leung, Yee-hong (IEEE, 2011)
Beamformers are known to be sensitive to errors and mismatches in their array elements. This paper proposes a robust steerable broadband beamformer design using the Farrow structure and for arbitrary array geometry. The design formulation includes stochastic models describing the flexibility for microphone errors. This method establishes a direct relationship in controlling the robustness specification in the design from given microphone characteristics. The robust design procedure optimises the mean performance of the beamformer. Design examples show significant reduction in error sensitivity in the robust design formulation.